Analisis Hubungan Nilai Indeks Zagreb dengan Titik Didih dan Kestabilan Senyawa Kerangka Dasar Calamenene - Sabil, M. Ibnu; Miftahurrahman, Miftahurrahman; Wardhana, I Gede Adhitya Wisnu; Dharmayani, Ni Komang Tri (Program Studi Matematika, Universitas Nusa Cendana, 2025)
A new compound, dysoxyphenol, isolated from Dysoxylum densiflorum, has acalamenene-based framework. The structure of dysoxyphenol is classified as a sesquiterpene. Thisstudy discusses the relationship between Zagreb Index values and the physical properties andstability of two compounds: calamenene and dysoxyphenol. The Zagreb Index, consisting of thefirst and second indices, is used to measure the structural stability of a graph through the sum ofsquared vertex degrees. The objective of this analysis is to determine the Zagreb Index values forcalamenene and dysoxyphenol, to measure the boiling points and stability of the compounds. Thisanalysis was carried out by examining the structures of calamenene and dysoxyphenol. The obtainedstructures were then analyzed graphically. The results of this study show that the first and secondZagreb Index values for calamenene are 262 and 340, which are smaller compared to the first andsecond Zagreb Index values for dysoxyphenol, which are 264 and 350, respectively. This indicatesthat calamenene has a lower boiling point than dysoxyphenol and is more stable than dysoxyphenol.